Mahasiswa S1 - Karen Yunika Dwiantono (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
PT. Aplikasi Karya Anak Bangsa, also known as Gojek, is a multinational tech company that achieved decacorn title in Southeast Asia. The main product of this company is a super app by the name of Gojek. This so- called super app offers many services, from online ojek (motorbike taxi), online car taxi, food delivery, courier, electronic wallet, and many more. As a company that focuses on mobile application, Gojek app interface plays an important role for the success of it’s company. However, after releasing it’s new update, version 4.0, Gojek has received many critcs regarding the app’s new interface. Many users report inconveniences with using Gojek app version 4.0 and above. Therefore, this article analyzes Gojek UX through usability testing and multiple resources. It is found that users’ complaints may came from three causes. The first cause is the abrupt change in Gojek interface, second is the complicated home page, and the third is slow application performance.